2006
DOI: 10.1007/s00213-006-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antipsychotic drugs as inhibitors of multidrug resistance transporter P-glycoprotein

Abstract: Pharmacokinetic interactions due to inhibition of P-gp activity by the antipsychotics appear possible and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 55 publications
(44 reference statements)
5
71
0
Order By: Relevance
“…3,11,12) This is the first report for a minimal role of P-gp in disposition of bupropion and its three major metabolites. Our results are in good agreement with our previous pharmacokinetic study in CF1 mice, in which risperidone, a substrate and inhibitor of P-gp 22,24,27) showed negligible effects on plasma and brain concentrations of bupropion and its metabolite HB. 22) The minimal involvement of P-gp in disposition of bupropion suggests that alteration of P-gp activity is not an important source for drug-drug interactions and variable therapeutic response of bupropion.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…3,11,12) This is the first report for a minimal role of P-gp in disposition of bupropion and its three major metabolites. Our results are in good agreement with our previous pharmacokinetic study in CF1 mice, in which risperidone, a substrate and inhibitor of P-gp 22,24,27) showed negligible effects on plasma and brain concentrations of bupropion and its metabolite HB. 22) The minimal involvement of P-gp in disposition of bupropion suggests that alteration of P-gp activity is not an important source for drug-drug interactions and variable therapeutic response of bupropion.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in good agreement with our previous pharmacokinetic study in CF1 mice, in which risperidone, a substrate and inhibitor of P-gp 22,24,27) showed negligible effects on plasma and brain concentrations of bupropion and its metabolite HB. 22) The minimal involvement of P-gp in disposition of bupropion suggests that alteration of P-gp activity is not an important source for drug-drug interactions and variable therapeutic response of bupropion. The major mechanism for previous reported alteration of bupropion plasma concentrations by other perpetration drugs is by changing of the metabolic enzyme activities of bupropion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Why the IC50 for the inhibition of AB by CPZ in intact cells decreased with incubation time and ultimately surpasses its IC50 for its direct effect on Complex I in isolated mitochondria is unclear. This is unlikely to relate to its behaviour as a blocker of P-GP mediated efflux since both HAL and RIS also block P-GP with potencies nearly identical to that of CPZ [19].…”
Section: Effect Of Antipsychotics On Mitochondrial Electron Transportmentioning
confidence: 98%